Delivery room management of ELBW infants in Italy - Rech Morassutti, Francesca; Satariano, Irene; Doglioni, Nicoletta; Criscoli, Giulio; Cavallin, Francesco; Gizzi, Camilla; Martano, Claudio; Ciralli, Fabrizio; Torielli, Flaminia; Villani, Paolo E.; Di Fabio, Sandra; Quartulli, Lorenzo; et al. (Acta Biomedica Atenei Parmensis, 2015)
In this article we evaluated the consistency of practice and the adherence to the International Guidelines in early delivery room management of ELBW infants in Italy. A polyethylene bag/wrap was used by 54 centres (55.1%). In Northern regions, one centre (2.5%) reported to use oxygen concentrations >40% to initiate positive pressure ventilation in ELBW infants. These proportions were higher in the Central (14.3%) and Southern (16.2%) areas. A T-piece device for positive pressure ventilation was widely used (77/97, 79.4%). A median of 13% (IQR: 5%–30%) of ELBW infants received chest compressions at birth in Italy. Forty-seven out of 98 (47.9%) centres declared to administer prophylactic surfactant in delivery room. Although there were geographic differences in the country, our results showed a good general adherence to the International Guidelines for Neonatal Resuscitation.